2014
DOI: 10.1371/journal.pbio.1001944
|View full text |Cite
|
Sign up to set email alerts
|

Action Potential Initiation in Neocortical Inhibitory Interneurons

Abstract: Sodium channels add variety to inhibitory interneurons Different populations of inhibitory interneurons in the cerebral cortex express distinct subtypes of sodium channels, resulting in diverse action potential thresholds and network excitability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 60 publications
(106 reference statements)
13
99
2
Order By: Relevance
“…If this hypothesis were correct, we would expect the missense variants observed in ASD to reduce Na V 1.2 channel function and decrease neuron excitability. We therefore performed functional analyses of all 12 de novo SCN2A mutations observed in the 4,109 ASD cases from the Simons Simplex Collection (SSC; 2,508 families with a single affected child) and Autism Sequencing Consortium (ASC; 1,601 families with one or more affected children), as these cases were identified as representing idiopathic ASD in clearly defined cohorts (4, 9, 22). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If this hypothesis were correct, we would expect the missense variants observed in ASD to reduce Na V 1.2 channel function and decrease neuron excitability. We therefore performed functional analyses of all 12 de novo SCN2A mutations observed in the 4,109 ASD cases from the Simons Simplex Collection (SSC; 2,508 families with a single affected child) and Autism Sequencing Consortium (ASC; 1,601 families with one or more affected children), as these cases were identified as representing idiopathic ASD in clearly defined cohorts (4, 9, 22). …”
Section: Resultsmentioning
confidence: 99%
“…Though the majority of cortical interneurons express SCN1A /Na V 1.1 at the AIS (46, 47), with loss of function resulting in Dravet Syndrome with EE (48), somatostatin positive interneurons, which play a role in cortical circuit maturation (49, 50), express a mix of both Na V 1.1 and 1.2 in the proximal AIS (9). Further, Na V 1.2 channels are expressed throughout cerebellar granule cell axons (8), potentially contributing to episodic ataxia (25).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the genes encoding the Na v 1.1 channels can cause Dravet syndrome and other types of infantile epilepsy [63] . In both PV and SST interneurons, Na v 1.6 channels were found in the distal part of the AIS, whereas Na v 1.2 channels were found in the proximal part of the AIS only in SST-positive INs [60] . A recent study showed that, in human cortical pyramidal cells, the pattern of Na + channel distribution is similar to that in rodents [64] .…”
Section: Na + Channelsmentioning
confidence: 93%
“…Other study suggests, however, that the distribution of Na v 1.6 within the AIS is more uniform [42] . Na v 1.1 channels are found in the proximal part of the AIS of the parvalbumin (PV)-and somatostatin (SST)-positive GABAergic interneurons [60] of the neocortex and cerebellum [42] , in retinal ganglion cells [61] and in spinal cord motor neurons [62] . Mutations in the genes encoding the Na v 1.1 channels can cause Dravet syndrome and other types of infantile epilepsy [63] .…”
Section: Na + Channelsmentioning
confidence: 99%
“…Dysfunction in one or more of these inhibitory neuron populations can disrupt both the feedback and feedforward inhibitory circuitry, resulting in epilepsy disorders (Khoshkhoo et al, 2017;Paz and Huguenard, 2015). NAV1.1 is predominantly localized in the soma and in the axon initiating segment of PV-positive neurons (Ogiwara et al, 2007) and to lesser extent in SST and VIP neurons (Goff and Goldberg, 2019;Li et al, 2014;Ogiwara et al, 2007;Tai et al, 2014). Reduced excitability of PV neurons has been implicated in hyperexcitable circuits in Scn1a mouse models of DS and GEFS+ (Dutton et al, 2013;Favero et al, 2018;Hedrich et al, 2014;Rubinstein et al, 2015a;Tai et al, 2014).…”
Section: Effects Of Scn1a Mutations On Neuronal Firingmentioning
confidence: 99%